The Students' Errors and Problems Encountered in Speaking Class at Harford Institute - Ndraha, Libertini Priskila; Sinaga, Nenni Triana; Pakpahan, Carolina (Lembaga Riset dan Inovasi Almatani, 2025)
This study aims to determine students’ errors and problems encountered in speaking class. This research was conducted at the Harford Institute, focusing on one class as the subject of analysis. This is a descriptive qualitative study, which seeks to describe the types of mistakes and difficulties students face during speaking activities. Data was collected through two primary techniques: observation and interviews, which provided comprehensive insights into the students' challenges. After collecting the data, the researcher then analyzed the data using Miles, Huberman and Saldana's (2014), which involves steps such as data reduction, data display, and conclusion drawing. With the results of 2 of interlingual errors, 8 of intralingual errors, 9 of lack of vocabulary, 20 of poor grammar, and 7 of poor pronunciation. The most common problem found is poor grammar and the fewest errors found are interlingual. The results highlight the importance of addressing these issues in speaking classes, particularly focusing on improving grammar and vocabulary, as these were the most prevalent problems encountered by students.